2000
DOI: 10.2308/accr.2000.75.3.327
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Audit Quality and Consequence Severity on Juror Evaluations of Auditor Responsibility for Plaintiff Losses

Abstract: This study investigates whether providing higher quality audits increases auditors' chances of avoiding legal liability. Negligence rules hold auditors responsible for plaintiff losses only when the quality of the audit provided fails to meet standards of care. The results of my experiment suggest that the ex post observed consequences of audit failure can affect the standards of care to which jurors hold auditors. Specifically, participants serving in the role of jurors assessed higher standards of care for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
141
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(149 citation statements)
references
References 15 publications
7
141
0
1
Order By: Relevance
“…Junior-level students were judged to be suitable participants because they are of legal age to serve on a jury. This is consistent with other jury research (e.g., Kadous 2000Kadous , 2001.…”
Section: Participantssupporting
confidence: 82%
“…Junior-level students were judged to be suitable participants because they are of legal age to serve on a jury. This is consistent with other jury research (e.g., Kadous 2000Kadous , 2001.…”
Section: Participantssupporting
confidence: 82%
“…Imagining such adjustments to the auditors' procedures, however, is more difficult when the auditors did not investigate for the fraud. This is important because evaluator awareness of specific actions that, if implemented, would have allowed the auditors to detect the fraud increases evaluators' belief that the fraud should have been detected (McMullen et al 1995;Roese 1997), which increases the severity of their assessments of auditor liability (Kadous 2000;Reffett 2010). …”
Section: Figure 1 Results From the First Experimental Packetmentioning
confidence: 99%
“…Financial statement users asked to assess a company's viability have been found to be prone to hindsight bias (Buchman, 1985). Jurors (Lowe & Reckers, 1994;Kadous, 2000;Kadous, 2001) and judges (Anderson et al, 1995;Anderson et al, 1997) asked to evaluate the actions of auditors have also been found to be prone to the bias. Brown and Solomon (1987) found that capital-budgeting decisions are influenced by outcome information.…”
Section: Presence Of Hindsight Biasmentioning
confidence: 99%